Application of Mangrove Processing as a Value-Added Product for The Community in Belinyu District, Bangka Regency - Irma Akhrianti; Occa Roanisca; Andi Gustomi (Jurnal Pengabdian Kepada Masyarakat Universitas Bangka Belitung, 2022)
Air Jukung Village is one of the villages located in Belinyu District, Bangka Regency, Bangka Belitung Islands Province which is rich in potential mangrove resources but has not been optimally utilized by the local community in the Covid 19 pandemic era. One of the potential developments of mangrove areas that can be used as superior products of Air Jukung Village is the utilization of perepat fruit and nipah fruit into syrup as a value-added product. The method of implementing this activity consists of preparation, implementation and evaluation. This service program has several stages of activities including 1) efforts to increase public understanding and awareness of the potential / benefits of mangrove fruit to be processed into value-added products through exploration and incidental socialization / counseling activities, 2) increasing community skills through providing training in making syrup from nipah fruit. This service activity provides good results where there is an increase in understanding, knowledge about the potential utilization, and skills in processing mangrove fruit into value-added products which are expected to become one of the superior products of the Belinyu Community that can improve the regional economy.